Driving development : a story of BRAC's evolution and effectiveness - Hossain, Mahabub, 1945-; Kairy, Shib Narayan; Bayes, Abdul (Dhaka : University Press Limited, 2016)
[The Bangladesh Rural Advancement Committee or] BRAC is now about 45 years old and this watershed moment provided an opportunity to reflect on the last four decades or so. More importantly, the aim is to look ahead for the challenges that would be confronted by BRAC. In the backdrop of these factors, this book inscribes the evolution of development interventions made by BRAC, including the mistakes made and the lessons learnt, in its efforts to contribute to socio-economic advancement of the country.--Publisher's website.
1. Introduction / Mahabub Hossain -- 2. Education: Facilitating Human Resource Development / Samir Ranjan Nath and Safiqul Islam -- 3. Reaching Healthcare to Grassroots / Syed Masud Ahmed, Kaosar Afsana, Akramul Islam and Faruque Ahmed -- 4. Maternal, Neonatal and Child Health / Hashima-E-Nasreen and Kaosar Afsana -- 5. Nutrition Interventions for Improved Child Health / Barnali Chakraborty and M Raisul Haque -- 6. Microfinance: Financial Inclusion for Employment Generation / Mahabub Hossain and SN Kairy -- 7. Challenging the Frontier of Poverty Reduction: Targeting the Ultra Poor / Mahabub Hossain, Anindita Bhattacharjee and Narayan C Das -- 8. Agriculture for Food Security / Mahabub Hossain, M Sirajul Islam, SC Nath, MA Saleque and Mokarram Hossain -- 9. Water, Sanitation, Hygiene and Disaster Management / Nepal C Dey, Tahera Akter, Sifat E Rabbi and Babar Kabir -- 10. Community Empowerment and Local Governance / Mohammad Rafi, Kazi Nazrul Fattah, Sharin Shahajahan Naomi and Anna Minj -- 11. Human Rights and Legal Aid Services / Mohammad Rafi, Sharin Shajahan Naomi and Faustina Pereira -- 12. Gender Justice and Women Empowerment / Sheepa Hafiza, Rumana Ali and Mohammad Rafi -- 13. Trajectory for Institutional Development / Abu Ahsan, Mohammad Rafi and Andrew Jenkins -- 14. Evolution of Development Management in BRAC / Sukhendra Kumar Sarkar -- 15. Governance, Transparency, Enterprises and Financial Sustainability / SN Kairy -- 16. Reflections on Drivers of BRAC Success / Salehuddin Ahmed -- 17. Research Driving Development / Ahmed Mushtaque Raza Chowdhury and Andrew Jenkins -- 18. Conclusion / Mahabub Hossain.
Includes bibliographical references and index.
AAL, BIED, GenEd
Keywords: BRAC (Organization); Rural development -- Bangladesh; Non-governmental organizations -- Bangladesh; Non-governmental organizations; Rural development; Education; Microfinance; Social sciences; Medical care; Bangladesh